2011
DOI: 10.1371/journal.pone.0019105
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Gamma Activated Macrophages Kill Mycobacteria by Nitric Oxide Induced Apoptosis

Abstract: Mycobacterium tuberculosis is an intracellular pathogen of macrophages and escapes the macrophages' bactericidal effectors by interfering with phagosome-lysosome fusion. IFN-γ activation renders the macrophages capable of killing intracellular mycobacteria by overcoming the phagosome maturation block, nutrient deprivation and exposure to microbicidal effectors including nitric oxide (NO). While the importance about NO for the control of mycobacterial infection in murine macrophages is well documented, the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
158
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(162 citation statements)
references
References 54 publications
2
158
0
2
Order By: Relevance
“…36 IFN-g sensitizes target cells to killing by diverse mechanisms, including modulation of HLA expression, 62,63 production of nitric oxide, 3 activation of caspase death pathways, [64][65][66] and induction of Fas expression. [44][45][46]67 We previously reported that Fas/FasL is the major cell death pathway for marrow destruction For personal use only.…”
Section: Cd48mentioning
confidence: 99%
See 1 more Smart Citation
“…36 IFN-g sensitizes target cells to killing by diverse mechanisms, including modulation of HLA expression, 62,63 production of nitric oxide, 3 activation of caspase death pathways, [64][65][66] and induction of Fas expression. [44][45][46]67 We previously reported that Fas/FasL is the major cell death pathway for marrow destruction For personal use only.…”
Section: Cd48mentioning
confidence: 99%
“…Its absence in genetically engineered mice and in humans with constitutional genetic defects profoundly influences susceptibility to microbial agents, especially chronic mycobacterial infection. [1][2][3][4] When immunity is triggered inappropriately, as in autoimmune diseases or immune-mediated syndromes such as graft-versus-host disease, [5][6][7] IFN-g appears to mediate inflammation and target cell destruction, negative effects associated with type 1 T cells and Th1 cell response. 8,9 However, the precise roll of IFN-g in animal models, and particularly in human diseases, has not always been easy to define because of conflicting data among experiments and sometimes strikingly poor correlation between murine experiments and the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…These data verify that DCP induction of the iNOS-NO effector pathway in human monocytes significantly contributes to suppression of intracellular mycobacteria. The mechanism(s) by which NO and/or RNI kill mycobacteria is unclear but has been suggested to involve disruption of bacterial DNA, proteins, signaling, and/or induction of monocyte/macrophage apoptosis (15,71). Furthermore, given that previously reported activities of DCP include the induction of apoptosis (20), there may be a connection between DCP-mediated NO production and apoptosis of infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-alpha can bind to extracellular domain of TNF-alpha receptor , and the cytoplasm domain can aggregate FADD and FLICE which can initiated the apoptosis; Another famous cytokine, IFN-, which can induce the macrophage apoptosis, plays a key role in clearance of the mycobacterium tuberculosis by inducing host cell apoptosis depended by the nitric oxide(NO). [19] TGF-1 acts as a chemoattractant and is very important for the immune response, this cytokine also play a predominant suppressive role in inhibiting the cell proliferation and stimulating B cells to apoptosis. [20] Above all, the cytokines are the positive inducer of apoptosis.…”
Section: Cytokinesmentioning
confidence: 99%
“…Mycobacterium can be cleared by macrophage's apoptosis which was induced by the NO and IFN- [28]; Chlamydia pneumoniae infection can induce the human T lymphocyte cell apoptosis, through this way, Chlamydia pneumonia could induce immunologic tolerance and would make pathogen persistence infection and inflammation [29]; Dendritic cells(DC) were well known immune cells, as an antigen-process cell, DC can inhibit pathogen replication and diffusion by caspase-3 dependent apoptosis in early infection stage, For instance, Legionella pneumophila was unable replicated in DC, because DC go to apoptosis when Legionella pneumophila infected these cells in the early stage. [30] Beside the bacteria infection induced the apoptosis, some virus also be found to involve in the apoptosis.…”
Section: Pathogen Effectorsmentioning
confidence: 99%